Sniffer mice discriminate urine odours of patients with bladder cancer: A proof-of-principle study for non-invasive diagnosis of cancer-induced odours. Issue 1 (December 2017) - Sato, Takaaki; Katsuoka, Yoji; Yoneda, Kimihiko; Nonomura, Mitsuo; Uchimoto, Shinya; Kobayakawa, Reiko; Kobayakawa, Ko; Mizutani, Yoichi
Abstract Similar to fingerprints, humans have unique, genetically determined body odours. In case of urine, the odour can change due to variations in diet as well as upon infection or tumour formation. We investigated the use of mice in a manner similar to "sniffer dogs" to detect changes in urine odour in patients with bladder cancer. We measured the odour discrimination thresholds of mice in a Y-maze, using urine mixtures from patients with bladder cancer (Stage I) and healthy volunteers (dietary variations) as well as occult blood- or antibiotic drug metabolite-modulated samples. Threshold difference indicated that intensities of urinary olfactory cues increase in the following order: dietary variation < bladder cancer < occult blood < antibiotic drug metabolites. After training with patient urine mixtures, sniffer mice discriminated between urine odours of pre- and post-transurethral resection in individual patients with bladder cancer in an equal-occult blood diluted condition below the detection level of dietary variations, achieving a success rate of 100% (11/11). Furthermore, genetic ablation of all dorsal olfactory receptors elevated the discrimination thresholds of mice by ≥ 105 -fold. The marked reduction in discrimination sensitivity indicates an essential role of the dorsal olfactory receptors in the recognition of urinary body odours in mice.